Chapter 5 Linguistic areas, bottom-up or top-down? The case of the Guaporé-Mamoré - Muysken, Pieter (De Gruyter, 2014)
In this paper we will take data from four areas of grammatical structure: argument marking (coded by Birchall), subordination (coded by Van Gijn), the noun phrase (coded by Krasnoukhova), and tame marking (tense/aspect/mood/evidentiality, coded by Müller). These data are compared for 22 lan-guages, thirteen from the Guaporé-Mamoré region in a broad sense, and nine from outside of the region. The key question we were originally asking our-selves is: do the thirteen languages from the region pattern more closely together than the overall set of languages as a whole, including the nine outsiders? It turned out that a somewhat different formulation was better, but we return to this below.